Architecture as an Extension of the Domain of Struggle. An Idea of Europe Revisited in View of Three Successive Concepts: Technocracy, Thanatopolitics and Thanatopraxia - Daniel Maurício Santos de Jesus (Histories of Postwar Architecture)
A few years after the original edition of Michel Houellebecq's book Extension of the Domain of Struggle, in the aftermath of the civil war and the subsequent balkanization of Yugoslavia, Lebbeus Woods accompanies a dystopian proposal for the "reconstruction" of the ruined city with the following statement: “Architecture and war are not incompatible. Architecture is war. War is architecture. I am at war with my time, with history, with all authority that resides in fixed and frightened forms.”[1] In view of the destruction and violence apparent in (his) forensic interpretation[2] of Sarajevo, Lebbeus Woods explains the competition proposal by placing it in the fight against the authority made explicit through materialized forms. In other words, understanding the conception and production of the architectural device as an activity that mediates the transformation of the habitable material support. And recognizing how it thrives within the inescapable framework of the relations of production in the neoliberal capitalist system. Hostage to the material purpose of building, instrumental for the confiscation and accumulation of private property, deconstructing or reconstructing, space production becomes an indispensable resource in perpetuating asymmetrical power relations – of a kind which an elementary political awareness distinguishes as socially and environmentally ruinous. Hence, a hypothesis arises from this alignment of propositions: the more a conceptual autonomy is claimed for the architectural project, the more the circumscription of its practice in its own disciplinary fiefdom is defended – under a technical and methodological determinant – the more it becomes vulnerable to plutocratic confiscation of financial, material, and technological resources in each era. It is in these terms that we can deduce, by extension, Architecture as an extension of the domain of struggle. Discarding the presumed ideological neutrality in favor of a concrete mediation, manifested in a series of references to documentary and fictional films that inscribe architecture from the outside in – such as Empire of The Sun (Steven Spielberg, 1987), Nuit et Bruillard (Alain Resnais, 1955), The Cook, The Thief, His Wife and Her Lover (Peter Greenaway, 1989) – and then some literary texts like High Rise (J.G. Ballard, 1975), we begin to distinguish the effects from the causes: ideological, political, economic and social meaning are extracted from "a collision between the characters and the physical support that shelters them", and intersected as a renewed compound, become fundamental for summoning collective resistance. [1] Lebbeus Woods, “Manifesto” from War and Architecture, New York: Princeton Architectural Press, 1993. (Retrieved January 19, 2024, from https://www.readingdesign.org/manifesto-lebbeus-woods). [2] The term forensic analysis refers to the work of Eyal Weizman's, founder of the Forensic Architecture Agency, which uses material transformations in architecture as material evidence for further judicial investigation and to bring actions in favor of human rights.